ANALISIS PREDIKSI KESULITAN KEUANGAN MENGGUNAKAN MODEL ALTMAN Z-SCORE - Nur Fadillah,; Selfira Salsabilla, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
This study aims to analyze the prediction of financial difficulties using the Altman Z-Score model in Companies Y and Z. This study uses quantitative descriptive analysis which aims to determine the value of each of the existing variables. The sample used in this study is Company Y and Z which are companies engaged in trading. This study uses secondary data in the statements of financial position and income statements for 2020 and 2021. The analytical method used is the Altman Z-Score method. Based on the results of the analysis, the results show that PT Y has increased to the yellow zone for 2021 with an overall index value of 0.82 to 1.33 while PT Z is still in the red zone with index value 0,29 in 2020 and 0,57 in 2021.